Cardiovascular parameters and neural sympathetic discharge variability before orthostatic syncope: role of sympathetic baroreflex control to the vessels. (23rd March 2015) - Barbic, Franca; Heusser, Karsten; Marchi, Andrea; Zamunér, Antonio Roberto; Gauger, Peter; Tank, Jens; Jordan, Jens; Diedrich, André; Robertson, David; Dipaola, Franca; Achenza, Sara; Porta, Alberto; et al.
Abstract: We tested the hypothesis that altered sympathetic baroreceptor control to the vessels (svBRS) and disrupted coupling between blood pressure (BP) fluctuations and muscle sympathetic activity (MSNA) discharge pattern in the low frequency band (LF, around 0.1 Hz) precede vasovagal syncope. Seven healthy males underwent ECG, BP, respiratory, and MSNA recordings at baseline (REST) and during a 15 min 80° head-up tilt, followed by a −10 mmHg step wise increase of lower body negative pressure up to presyncope. Spectral and coherence analyses of systolic arterial pressure (SAP) and MSNA variability provided the indexes of vascular sympathetic modulation, LFSAP, and of the linear coupling between MSNA and SAP in the low frequency band (around 0.1 Hz), K 2 MSNA-SAP (LF). svBRS was assessed as the slope of the regression line between MSNA and diastolic arterial pressure (DAP). Data were analyzed at REST, during asymptomatic and presyncope periods of tilt. svBRS declined during presyncope period compared to REST and asymptomatic tilt. The presyncope period was characterized by a decrease of RR interval, LFMSNA, LFSAP, and K 2 MSNA-SAP (LF) values compared to the asymptomatic one, whereas MSNA burst rate was unchanged. The reduction of svBRS producing an altered coupling between MSNA and SAP variability at 0.1 Hz, may provoke circulatory changes leading to presyncope.